Animal-Assisted Therapy in Middle-Aged and Older Patients With Schizophrenia: A Randomized Controlled Trial - Chen, Tzu-Ting; Hsieh, Ton-Lin; Chen, Mei-Li; Tseng, Wei-Ting; Hung, Chi-Fa; Chen, Chyi-Rong (Frontiers in Psychiatry, 2021)
Objective: Animal-assisted therapy (AAT) has the potential to improve the symptomology, negative emotions, and level of well-being in older adults, as well as patients with mental illness. However, there remains limited evidence supporting the treatment efficacy of AAT in middle-aged and older adults with schizophrenia. Therefore, this study implemented a randomized controlled trial to assess the efficacy of a 12-week AAT psychological intervention with dogs for middle-aged and older patients with chronic schizophrenia in a clinical setting. Method: Patients, age≥40 years, with chronic schizophrenia were allocated randomly to either the AAT group or control group. Patients in the AAT group received an additional hour -long AAT session every week for 12 weeks. Patients in the control group received the usual treatment plus an hour long non-animal related intervention. All patients were assessed based on primary outcome measures before and after the 12-week intervention, including the Positive and Negative Syndrome Scale (PANSS), Depression Anxiety Stress Scales Assessment (DASS), and Chinese Happiness Inventory (CHI). Results: Patients who received AAT had greater improvements in the PANSS and DASS-stress subscale scores than the control group (p < .05). The effect was small (success ratio different, SRD = 0.25) for the PANSS and the DASS-stress subscale (SRD = 0.15). There were no significant differences in the change scores of the CHI between the AAT and control groups (p = 0.461). Conclusions: AAT seemed to be effective in reducing psychiatric symptoms and stress levels of middle-aged and older patients with schizophrenia. AAT could be considered as a useful adjunctive therapy to the usual treatment programs.